PENGEMBANGAN LKPD MENGGUNAKAN LIVEWORKSHEET UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Zai, Firman Pikir; Mendrofa, Ratna Natalia; Mendrofa, Netti Kariani; Lase, Sadiana (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Early studies show that: (1) students' mathematical abilities are in the category of lacking; and (2) The learning process still does not utilize technology in an integrated manner. Therefore, LKPD was developed using a liveworksheet to overcome these problems. The purpose of this research is to develop a valid, practical and effective LKPD to improve students' mathematical problem-solving skills. This research uses the ADDIE (analyze, design, development, implementation, evaluation) development model. The instruments in this study are learning outcome tests, material expert validation questionnaires, linguist validation questionnaires, media expert validation questionnaires, teacher response questionnaires and student response questionnaires. Based on the results of the research, the LKPD developed has been tested and declared valid both in terms of material validity, language validity and media validity. Furthermore, the LKPD is also very practical based on the results of the teacher response questionnaire and the student response questionnaire. The LKPD developed is also effective in improving students' mathematical problem-solving skills, as seen from the test scores of student learning outcomes. Thus, it can be concluded that LKPD using the liveworksheet developed has met the expectations or objectives of the research.